Designing core–shell metal–organic framework hybrids: toward high-efficiency electrochemical potassium storage. Issue 46 (17th November 2021) - Yu, Dongbo; Song, Qingjing; Cui, Jiewu; Zheng, Hongmei; Zhang, Yong; Liu, Jiaqin; Lv, Jun; Xu, Tongwen; Wu, Yucheng
Abstract : Due to the unique core–shell structure which enables mutual advantage complement of the core and the shell, the electrochemical K + storage property of core–shell MOF-derived nanoporous carbon is superior to that of single MOF-derived counterparts. Abstract : Nanoporous carbon derived from metal–organic frameworks (MOFs) is an attractive electrode material for potassium ion batteries, but carbon electrodes fabricated using single MOF precursors cannot balance all the demands. In view of the core–shell nanostructure that can complement the advantages of the core and shell materials, we here demonstrate a facile and general synthesis strategy for synthesizing a series of core–shell MOF hybrids. The prepared core–shell MOF hybrids are applied as precursors for nanoporous carbon which maintain a core–shell hybrid structure after carbonization, having electrically conducting carbon as the core and N-doped carbon as the shell. Due to the unique core–shell structure which offers more active sites and fast reaction kinetics, the electrochemical K + storage properties of all core–shell MOF hybrid-derived nanoporous carbon are superior to those of single MOF-derived counterparts. Our synthesis strategy of core–shell MOF hybrids is expected to provide a useful reference for other MOF nanostructures, and the enhanced K + storage performance also reveals the significance of MOF structural engineering.